Exploring Seaweed Cultivation in the Marine Environment and Its Interaction with Microplastic - Cham, Mbara; Yasman, Yasman (BIOEDUSCIENCE, 2025)
Background: Seaweed cultivation in marine environments offers ecological and economic benefits, but the increasing presence of microplastics poses risks. This review explores cultivation techniques and the impact of microplastic pollution on seaweed growth, nutrient absorption, and health. Methods: Literature was sourced from Google Scholar and academic databases using keywords related to seaweed cultivation and microplastic pollution, focusing on peer-reviewed articles, books, and credible reports from the past decade. Studies were selected based on methodological rigor, relevance, and source credibility. The literature was synthesized to highlight key patterns, trends, and knowledge gaps on the impact of microplastic pollution on seaweed farming. Results:  Seaweed aquaculture provides food, biofuel, pharmaceuticals, and environmental benefits, varying cultivation methods by species, environment, and product. Despite growing demand, microplastic pollution threatens seaweed farming and marine ecosystems. This study explores seaweed’s role in microplastic retention, its potential as a bioindicator, and its broader impact on marine health. Urgent action is needed to address plastic and microplastic emissions and mitigate long-term environmental and health risks. Conclusions: Seaweed aquaculture provides food, biofuel, and ecological benefits. However, microplastic pollution threatens its sustainability. Immediate action is required to address plastic pollution, as it poses long-term risks to marine ecosystems and human health. Governments are increasingly focusing on mitigation measures to address these pressing issues.